The prevalence of myopia and eye health behaviors among 3 to 18 years: a cross-sectional survey study - Lu Tian; Mengxia Zhu; Yuhan Song; Yin Wang; Yan Jiang (BMC Public Health)
Abstract Aims To determine the current status of self-reported myopia and the relationship between eye health behaviors and myopia in children and adolescents aged 3 to 18 years. Methods Children and adolescents aged 3–18 years from 15 schools were selected for the survey between January and June 2024 in Hubei Province, China. A stratified random cluster sampling method was employed for the collection of samples. All participants were requested to complete the Eye Health Behavior Assessment Scale for Kindergarten and Primary School Students in Grades 1-3-Parent Version (EHBAS-P) and the Eye Health Behavior Assessment Scale for Primary School Students in Grades 4–6 and Middle School Students-Student Version (EHBAS-S) online. Data on socio-demographic factors (gender, grades, region) and myopia rate were collected. Results A total of 3500 participants were invited, and 3240 usable questionnaires were collected (response rate, 92.57%). The overall prevalence of self-reported myopia among children and adolescents aged 3–18 years in Hubei Province was 34.35%. Risk of myopia was higher in females than in males (OR = 1.27, P = 0.007), in rural than in urban areas (OR = 1.88, P < 0.001), and in children with myopic parents than with non-myopic parents (OR = 3.21, P < 0.001). Furthermore, of the 3240 participants, only 18.1% (n = 587) had good eye health behavior levels, 46.1% (n = 1494) had moderate eye health behavior levels, and the rest had poor levels, and there was a significantly higher risk of myopia for poor compared to good eye health behavior levels (OR = 1.74, P < 0.001). The regression analysis showed that the level of eye health behaviors varied significantly with many of the demographic variables particularly with grades group, gender and whether myopia. Conclusion The prevalence of self-reported myopia is at a high level among individuals between the ages of 3 and 18 in Hubei province, China, with notable differences between urban and rural populations. The level of eye health behaviors among children and adolescents is suboptimal. A particular focus on fostering the development of positive eye-use habits among younger children should be reinforced in the future.